This concept will help reinforce the theory of addition and will also set up base for Introductory Algebra. Here a addition expression is provided with one missing number. You have to use the concept of addition to find the number which fulfills the expression correctly.

This types of questions are tricky as they are not that straightforward and you need to have good command of numbers and counting.

Let us consider some examples of his type of problem

Example 01
Fill in the blanks with suitable number
2 + ____ = 7

Here, we have number 2 with us.
Now what number will it take to make number 7 ?

If we add 2 with 5 we will get 7
Hence 5 is the right answer

Example 02
Find the missing number for below addition expression
5 + ______ = 9

Here we have number 5 with us
Now what number will it take to make final number 9

If we add number 4 to number 5 we will get 9
5 + 4 = 9

Now you have understood one example, it is now time to solve some questions.

### Find Missing number in Addition

(01) 7 + _____ = 10

Solution
a. we have number 7 with us
b. If we add 3 to 7 we will get number 10
Hence, 3 is the right answer

7 + 3 = 10

(02) 2 + _____ = 6

Solution
a. we have number 2
b. if we add 4 to 2, we will get number 6

2 + 4 = 6
Hence, 4 is the right answer

(03) 0 + _____ = 9

Solution
(a) we have number 0 with us
(b) If we add number 9 to 0, we will get number 9

0 + 9 = 9
Number 9 is the right answer

(04) 7 + ______ = 10

Solution
⟹ we have number 7 with us
⟹ How many more we need to make the number 10 ?

⟹ 7 + 3 = 10

(05) 2 + ____ = 4

Solution
(a) we have number 2 with us
(b) if we add 2 to 2, we will get number 4

2 + 2 = 4
Hence, Number 2 is the right answer

(06) ______ + 4 = 7

Solution
we have number 4 with us
If we add number 3 to 4, we will get 7

3 + 4 = 7
Number 3 is the right answer

(07) 4 + ______ = 8

Solution
we have number 4 with us
If we add 4 to 4, we will get number 8

4 + 4 = 8
Hence 4 is the right answer

(08) _______ + 5 = 5

Solution
we have number 5 with us
In order to get 5, add 0 to the existing number

0 + 5 = 5
Hence 0 is the right answer

(09) 2 + ______ = 3

Solution
we have number 2 with us
If we add 1 to 2, we will get number 3

2 + 1 = 3
Hence 1 is the right answer

(10) 8 + ______ = 9

Solution
we have number 8 with us
If we add number 1 to 8, we get number 9

8 + 1 = 9
Number 1 is the right answer

Find the missing number in the below addition expression

(01) 2 + ________ + 7 = 14

Solution
Step 01 : Add the existing number first
⟹ 2 + 7 = 9

Step 02: Rewrite the Addition Expression
⟹ 9 + _____ = 14

We have number 9 with us
If we add number 5 in the expression, we will get 14
⟹ 9 + 5 = 14

Hence number 5 is the right answer
The Final Expression is ⟹ 2 + 5 + 7 = 14

(02) 4 + _____ + 6 = 12

Solution
Step 01: Add the existing number present
⟹ 4 + 6 = 10

Step 02: Rewriting the expression
⟹ 10 + _____ = 12

We have number 10 with us
If we add number 2, we will get 12 as a result
⟹ 10 + 2 = 12

Hence 2 is the right answer
& the final expression is:
⟹ 4 + 2 + 6 = 12

(03) 3 + _______ + 4 = 11

Step 1: Add the existing number first
⟹ 3 + 4 = 7

Step 2 : Rewriting the addition expression
⟹ 7 + ______ = 11

We have number 7 with us
If we add number 4, we will get number 11
⟹ 7 + 4 = 11

Hence number 4 is the right answer
The Final Expression is ⟹ 3 + 4 + 4 = 11

(04) 6 + _______+ 3 = 19

Solution
Step 01 : Add the existing number first
⟹ 6 + 3 = 9

Step 02: Rewriting the addition expression
⟹ 9 + ______ = 19

We have number 9 with us
If we add number 10 then we will get number 19
⟹ 9 + 10 = 19

Hence 10 is the right answer
The Final Expression is 6 + 10 + 3 = 19

(05) 8 + _______ + 5 = 15

Solution
Step 01 : Add the existing Number
⟹ 8 + 5 = 13

Step 02: Rewrite the addition expression
⟹ 13 + ______ = 15

We already have 13 with us
If we add number 2, we will get 15 as final number
⟹ 13 + 2 = 15

Hence 2 is the right answer
The final expression is ⟹ 8 + 2 + 5 = 15

(06) 5 + _______ + 5 = 12

Solution
⟹ 5 + 5 = 10

Step 02: Rewriting the addition expression
⟹ 10 + _____ = 12

We already have number 10 with us
If we add number 2, we will get 12
⟹ 10 + 2 = 12

Hence 2 is the right answer
Final Expression is ⟹ 5 + 2 + 5 = 12

(07) 1 + _______ + 6 = 9

Solution
Step 01: Add Existing number present
⟹ 1 + 6 = 7

Step 02: Rewriting the addition expression
⟹ 7 + _______ = 9

We already have number 7 with us
If we add number 2, we will finally get number 9
⟹ 7 + 2 = 9

Hence 2 is the right answer
Final Expression is 1 + 2 + 6 = 9

(08) 3 + _______ + 5 = 11

Solution
Step 1 : Add the existing number present
⟹ 3 + 5 = 8

Step 2 : Rewriting the addition expression
⟹ 8 + ______ = 11

We already have number 8 with us
If we add number 3, we will get 11

Hence 3 is the right answer
Final expression is ⟹ 3 + 3 + 5 =11

(09) 2 + _______ + 3 = 5

Solution
Step 01 : Add the existing number
⟹ 2 + 3 =5

Step 02: Rewriting the addition expression
⟹ 5 + ______ = 5

We already have number 5 with us
If we add number 0, we will get 5
⟹ 5 + 0 = 5

Hence 0 is the right answer
Final expression is 2 + 0 + 3 = 5

(10) 3 + _______ + 9 = 20

Solution
Step 01: Add the existing number
⟹ 3 + 9 = 12

Step 02: Rewrite the addition expression
⟹ 12 + ______ = 20

We have number 12 with us
If we add number 8, we will get number 20
⟹ 12 + 8 = 20

Hence 8 is the right answer
Final Expression is ⟹ 3 + 8 + 9 = 20